2021
DOI: 10.22161/jhed.3.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits of adolescents in higher secondary school in Bhutan: An In-Depth Analysis of Nationally Representative Data

Abstract: Bhutan is a small landlocked country that lies between the two most populous countries in the world India and China, with a total area of 38,394 square kilometers. A peaceful mountainous kingdom in the Himalayas mandated free education to all children of school-going age up to the 12 th standard. Recognizing that education is the fundamental link to national progress, the Royal Government of Bhutan has always and will continue to emphasize education as a priority sector, In doing so, through a dynamic professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Education ministry 2018 reported that no decline was being observed in junk food consumption among high school students of Bhutan. 33 The dining out culture is witnessing an increase in the Indian society. there is steady growth in the fast-food sector in India as the number of people eating out has increased.…”
Section: Trends In South Asiamentioning
confidence: 99%
“…Education ministry 2018 reported that no decline was being observed in junk food consumption among high school students of Bhutan. 33 The dining out culture is witnessing an increase in the Indian society. there is steady growth in the fast-food sector in India as the number of people eating out has increased.…”
Section: Trends In South Asiamentioning
confidence: 99%